Factors influencing pregnancy stress in pregnant women in Korea: a cross-sectional study - Sook Jung Kang; Min Ji Yang (Korean Society of Women Health Nursing, 2022)
Purpose The purpose of this study was to investigate the association between maternal knowledge and social support on pregnancy stress among pregnant women in Korea. Methods The participants in this study were 148 pregnant women in Korea, recruited from online communities on pregnancy and/or childbirth, from June 2019 to April 2020. The collected data were analyzed using the independent t-test, one-way analysis of variance, Pearson correlation coefficient, and multiple regression. Results Participants were at average 18.25±8.28 weeks gestation, 56% were in the second trimester, 31% had one or more health issues in the current pregnancy (e.g., hyperemesis gravidarum), and 76% were first-time mothers. Participants had moderate levels of pregnancy stress (mean, 23.09±7.11 points out of 48) and maternal knowledge (mean, 14.42±4.67 points out of 21), whereas social support was somewhat high (mean 45.88±7.81 points out of 60). Pregnancy stress was weakly negatively correlated with social support (r=-.37, p<.001). Main source of pregnancy information (β=-.21, p=.011), marital satisfaction (β=-.18, p=.036), and social support (β=-.19, p=.038) were identified as significant factors affecting pregnancy stress, and these variables had an explanatory power of 22.7% for pregnancy stress. Conclusion Based on these findings, nurses should assess pregnancy-related stress during pregnancy and consider main source of pregnancy information and marital satisfaction when providing education or counseling. Moreover, strategies to reduce pregnancy stress through social support are needed to improve the quality of life for pregnant women.